A STUDY ON THE USE OF TOPICAL VERSUS INTRAVENOUS TRANEXAMIC ACID IN MINIMIZING BLOOD LOSS IN PRIMARY TOTAL KNEE REPLACEMENT IN A TERTIARY CARE HOSPITAL - HASEEB, M; MATEEN, M; RIAZ, A; SHOAIB, R; JUNAID, M; NAZ, KA (Biological and Clinical Sciences Research Journal, 2024)
Significant blood loss during total knee replacement (TKR) surgery is a major concern, with tranexamic acid (TXA) commonly used to reduce it. This study compares the efficacy of topical versus intravenous TXA in minimizing blood loss in primary TKR. Objective: To compare the efficacy of topical versus intravenous tranexamic acid in minimizing blood loss in primary total knee replacement surgery. Methods: This prospective randomized controlled trial was conducted at the Department of Orthopedics, CMH Rawalpindi, Pakistan in the duration from December 2023 to May 2024 to compare the efficacy of intravenous and intra-articular Tranexamic Acid (TXA) in primary total knee replacement (TKR) patients. 120 adult patients with primary knee osteoarthritis were randomly assigned to two groups: Group A (IV TXA) received 15 mg/kg TXA intravenously twice, and Group B (IA TXA) received 2 grams of TXA intra-articularly. Exclusion criteria included conditions like hepatitis B or C, TXA allergy, and severe medical histories such as thromboembolic events. Surgeries were performed by a single consultant orthopedic surgeon using a mid-vastus approach and cemented prosthesis, with standardized postoperative care, including drain management and rehabilitation exercises. Data on drain output, hemoglobin levels, and transfusion requirements were collected and analyzed using SPSS version 23, with statistical significance set at p < 0.05. Ethical approval and informed consent were obtained before the study. Results: In this study involving 120 patients undergoing total knee replacement (TKR), participants were evenly divided into Group A (Intravenous TXA) and Group B (Topical TXA). Both groups were comparable in demographics, procedural characteristics, and co-morbidities, ensuring balanced baseline conditions. Results showed that while Group B exhibited significantly less blood loss on Day 1 post-surgery (p = 0.15), there were no significant differences in immediate post-surgery blood loss, hemoglobin levels, or the need for transfusions. Postoperative complications, hospital stay length, and patient satisfaction were similar between the groups. Group B showed a trend towards a shorter hospital stay and better range of motion at six weeks. Conclusion: Our research demonstrates that topical and intravenous Tranexamic Acid (TXA) is equally effective in reducing intraoperative and postoperative blood loss in primary total knee replacement (TKR). No significant differences were observed between the two methods regarding hemoglobin level changes, transfusion rates, blood loss, complications, hospital stay duration, patient satisfaction, or functional outcomes. However, topical TXA offers advantages such as local application, enhanced safety, and ease of administration. These findings support the TXA delivery method based on patient preferences and characteristics, providing flexibility in clinical practice for managing blood loss in TKR.